Word recognition and content comprehension of subtitles for television by deaf children - Soledad Zarate; Joseph Eliahoo (JoSTrans: The Journal of Specialised Translation)
This project explores how deaf children read subtitles on television. The participants – recruited from years 3 to 6 of a mainstream school with a hearing impairment unit – were exposed to both broadcast and enhanced subtitles and their performances were compared. In particular, the focus is on identifying enhancements that can help children to understand subtitle content and to recognise new or difficult words. Among the enhancements introduced were repetition and highlighting of new or difficult words through the use of a bigger and different typeface, use of longer reading times, text reduction and careful spotting. This pilot study provides some useful information for future empirical experimental research on subtitling for deaf children.